Network Analysis of Organizations Providing HIV Services in Chicago: Toward an Integrated Response to the HIV Epidemic. Issue 2 (March 2022) - Phillips, Gregory; Lindeman, Peter; Janulis, Patrick; Johnson, Amy K.; Beach, Lauren B.; Stonehouse, Patrick; Kern, David; Boegner, Joshua; Raman, Anand; Greene, George J.
Abstract : Context: The public health response to the HIV epidemic has increasingly centered on the uptake of and adherence to biomedical interventions (eg, pre-exposure prophylaxis [PrEP], treatment as prevention [TasP]). Traditionally, various community and health care organizations have worked to address different stages of PrEP or TasP care. Objective: To understand the importance of how HIV prevention organizations providing these services interact to provide the comprehensive care needed for successful HIV and PrEP continuum outcomes. Design: Utilizing an Organizational Network Survey, network ties were examined between formal and informal partnerships among community agencies. Setting: This study examined community agencies in the current HIV prevention system in Chicago. Participants: Seventy-two community agencies across the Chicago metropolitan area. Main Outcome Measures: Using network analysis, this study examined ties between community agencies and assessed perceptions of collaboration and competitiveness in the current HIV prevention system in Chicago. Results: Overall, respondents reported that the current environment of HIV prevention in Chicago was extremely (18.8%), moderately (37.5%), or somewhat collaborative (37.5%) and extremely (68.8%) or moderately competitive (25.0%). The majority of partnerships reported were informal, with less than a quarter being formalized. That said, those who reported formal partnerships reported being satisfied with those relationships. There was a significantly negative association between density and perceived collaboration—grantees experiencing a more collaborative also reported less dense networks. Conclusion: These findings indicate that, despite perceived competitiveness, agencies are willing to work together and create a cohesive HIV prevention and treatment system. However, more work should be done to foster an environment that can support the formation of partnerships, to improve a coordinated response to providing HIV care, and sustain mutually beneficial relationships.